Pistang Pamana, Pistang Naaayon: A Socio-cultural and Environmental Sustainability Framework for Town Fiestas - Bandala, I (KnE Social Sciences, 2018)
Town fiestas have increasingly responded to the challenges posed by sustainable development. This study developed a framework for town fiestas which highlight its social, cultural and environmental sustainability by experiencing, exploring and analyzing its practices. Although none of these fiestas are identical, some consistent patterns emerged to demonstrate that comparisons can be developed. Each community has an ongoing challenge of determining how their fiesta can best meet its needs presently and in the future. Each is trying to keep pace with the changes that are taking place within their communities, within the region and from external forces. This study generated new knowledge: tracking the changes occurring in town fiestas in the Tagalog Region that a framework for sustainability was put together. This paper is a multiple case study which is highly ethnographic quantitative and qualitative in nature. In developing the framework, a survey of a sample of residents and tourists were administered for the selected fiestas. Purposive sampling was administered to gather first hand information from the main organizers/drivers of the fiesta: the tourism administrator, hermana mayor, LGU representative and church leaders. Lastly, participant observation method of research was employed. The framework formed composed of three components, the socio-cultural elements, the environmental elements and the multi-stakeholders collaborating strategies. Each of the fiesta observed has its own strengths and weaknesses. The framework linked the fiestas together and elements for sustainability were identified. For any fiesta to thrive, it has to resolve its threats and be able to identify and respond to the requisites of sustainability. Keywords: Cultural, Environmental, Social, Sustainability, Town Fiesta